Relationship Between Family Income and Food Insecurity Regarding Underweight Incidents in Children Under 5 Years Old, In 2024 - Santos Amaral, Jessica dos; Conceicao Pacheco, Aniceto da; Elvis Fatima, Tomas; Magno, Jerminal; Carvalho, Marcos; Anatolia Soares Maia Exposto, Levi (Rifa'Institute, 2025)
Introduction: Based on the Food and Nutrition Survey of Timor-Leste 2020, it was shown that most children under five years old in 13 municipalities are suffering from underweight issues at a rate of 32.4%. In Dili municipality, the prevalence of underweight is reported at 27.4%. Objective: This research is to understand the relationship between family income and food insecurity concerning underweight occurrences in children under five years old. Method: Research method utilized is a quantitative descriptive method with a cross- sectional approach. The population consists of mothers with children under five years old, totaling 274, with a sample size of 73 for the study. Result and Discussion: The univariate analysis shows that 56% of families have low income, and food insecurity is prevalent, with 26% experiencing severe insecurity. Based on food recall, 60% have poor food security, while the FFQ indicator shows 63% in poor condition. Underweight malnutrition affects 22% of children, with 55% experiencing poor nutrition. Family income significantly correlates with underweight cases (p=0.02), and food insecurity is also significant (p=0.01). The multivariate analysis shows an R-squared value of 20.2%. Conclusion: Research in Fomento II Village, Dili, in 2024 confirms a significant relationship between family income, food insecurity, and underweight cases in children under five